Ecological and phytocoenotical evaluation of post-reclamative dynamics of forest vegetation of Volynia Polesye - Блінкова, О. І. (Problems of Environmental Biotechnology, 2017)
The article deals the assessment of forest vegetation of Volynia Polesye on impact of drainage and reclamation of wetlands. The structural and functional components of the forest ecosystem were analyzed by removal distance from drained peatland and silted channels, where was began the process of secondary swamping. It has be found that phytosanitary and vitality stand structures; bio- and ecomorphological range of herbal vegetation violated at a distance of 50–100 meters.